EFEKTIVITAS TERAPI TUINA CHUZHEN MEDITATIF, AKUPUNTUR DAN FOOD TERAPI PADA METRORARGIA - Yelini Fan Hardi; Yusti Ariyani; Frisca Desma Ayu Kusuma Wardani (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2022)
Background : Maternal mortality (MMR) and child mortality (AKA) are strongly correlated with the health of women's reproductive organs. (Manuaba, 2009). Due to the effect on various parts of life and how it affects the State's ability to provide health services to the community, reproductive health issues become a problem that affects everyone, not just the person who is affected. (Manuaba, 2009). Objective: Understanding the Impact of Tuina Chuzhen Food Therapy, Acupuncture, and Meditation on Metrorageia Method : This study applies the Metroragia demonstration technique. Result : According to TCM, illness is viewed as an imbalance of energy that needs to be corrected in order to be treated. Keywords : Metroragia, akupuntur, tuina chuzhen, Traditional Chinese Medicine